2006
DOI: 10.1177/1359105306063313
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Women with Alcohol Problems Binge Eat?

Abstract: Questionnaires assessing heavy drinking and binge eating were administered to 58 women with alcohol problems. A sub-sample of the binge-eaters then participated in qualitative interviews about their perceptions of the connections between their two problems. Seventy-one percent self-identified as binge-eaters with most reporting 'severe' binge eating. Binge-eaters were younger, more frequent drinkers and drank more often for emotional relief than non-binge-eaters. Binge eating and heavy drinking appeared to ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 38 publications
1
11
0
1
Order By: Relevance
“…Psychoactive substances may also be used to help regulate painful affect [27]. In a review of the literature, Holderness et al (2004) found that rates of amphetamine use were found to be higher in patients with AN compared with BN [17].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychoactive substances may also be used to help regulate painful affect [27]. In a review of the literature, Holderness et al (2004) found that rates of amphetamine use were found to be higher in patients with AN compared with BN [17].…”
Section: Reviewmentioning
confidence: 99%
“…Questions should specifically explore the misuse of substances as weight loss mechanisms, for example, caffeine, tobacco, insulin, thyroid medications, stimulants or over the counter medications (laxatives, diuretics) used for metabolism restriction, caloric restriction, appetite suppression or purging [11,36,37]. Similarly, the role of alcohol or psychoactive substances in emotional regulation should be explored, for example, the use of alcohol, opiates or cannabis for the relief of anxiety, depression, guilt or shame, or for emotional reward [27]. Wolfe and Maisto (2000) highlight the importance of a behavioural assessment (including questionnaires, self-monitoring, role play and collection of collateral information) in order to explore the functional relationship between substance use patterns and ED behaviours.…”
Section: Reviewmentioning
confidence: 99%
“…Problematic food consumption and problematic alcohol consumption are often comorbid (Braun et al, 1994; Dunn et al, 2002; Grilo et al, 1989; Stewart et al, 2006; Taylor et al, 1993). This comorbidity can result in greater physical health problems and higher mortality risk (Dunn et al, 2002; Hingson et al, 2005; Hudson et al, 2007; Stewart et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This comorbidity can result in greater physical health problems and higher mortality risk (Dunn et al, 2002; Hingson et al, 2005; Hudson et al, 2007; Stewart et al, 2006). Considering the harmful consequences associated with such a comorbidity (Hudson et al, 2007; Stewart et al, 2006), a better understanding of food and alcohol co-consumption could inform effective treatment and prevention approaches (Sinha & O’Malley, 2000). …”
Section: Introductionmentioning
confidence: 99%
“…Acredita-se que o consumo diminuído de álcool na TPM das pacientes da amostra deste trabalho pode ser conferido ao fato de elas estarem em tratamento, ou, ainda, por saberem dos objetivos da pesquisa. (Hebert et al, 1995;Krestch et al, 1999;Taren et al, 1999 (Brasiliano, 2005;Krahn et al, 2006;Stewart et al, 2006). Apesar de menos prevalentes (10%), os transtornos alimentares apresentaram-se em taxas maiores do que na população em geral, nesta, estimada em 2 a 5% (Hay, 1998;Hay, 2002 Tobin et al (1994), num trabalho semelhante, teve como amostra 21 pacientes e mais 16 controles.…”
Section: Diferenças Relevantes Encontradas Entre Os Clusters I E Iiunclassified